Color stability of a nanofilled resin: influence of polishing and finishing and fluoride solutions according to time - Oliveira, Ana Luísa Botta Martins de [UNESP]; Santos, Patrícia Aleixo dos; Campos, Juliana Alvares Duarte Bonini [UNESP]; Botta, Ana Carolina; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (My University, 2014)
Aim: The aim of the study was evaluate the finishing and polishing effect of the color stability of the composite resin Filtek Supreme XT, according to different fluoride solutions and time. Material and Methods: Specimens were prepared (n=140) with half of the samples finished and polished. The experimental groups were divided according to the presence or absence of finishing and polishing and immersion solutions (artificial saliva, sodium fluoride solution at 0.05% - manipulated, Fluordent Reach, Oral B, Fluorgard). The specimens remained in artificial saliva for 24 hours and were subjected to an initial color analysis using a spectrophotometer CIELab system. Then, they were immersed in the experimental solutions for 1 minute a day. The readings of the color change were made after 24 and 48 hours, 7, 14, 21, 30 and 60 days after the first immersion. The three-way mixed Analysis of Variance (ANOVA) ("finishing/polishing", "immersion medium" and “time”) were performed. For multiple comparisons, the Sidak test for repeated measure was used, with a 5% level of significance. Results: The finishing and polishing factor showed significant variability, independently of the immersion media (p<0.001). Cconclusion: Finishing and polishing procedures yielded better color stability to composite resin over time, regardless of the immersion media.
Keywords: Dental polishing; Fluorine; Color; Composite resins